Perspectives on Native American Imagery from Students at a Premiere Tribal University - Scola, Zach; Wilkerson, Zach; Brian S. Gordon (Journal of Amateur Sport, 2022)
Haskell Indian Nations University is the sole 4-year intertribal university in America and their athletics department is called The Fightin’ Indians. Their logo and name seem to contradict most of the research describing the negative impacts of Native imagery. Interviews were conducted with current students at Haskell University to understand their feelings towards Native imagery overall. When exploring the usage of Native imagery by Haskell it was apparent the students felt as an all-Native institution there was a sense of ownership to utilize the imagery but were aware it misrepresented some Native people. The students also discussed how their imagery may influence outsiders’ perspectives. This study helps us understand a unique situation and should lead to future research around Native American imagery in sport.